Clinical and treatment profiles of arterial hypertension in Mexico during the COVID-19 pandemic: a cross-sectional survey endorsed by the “Collaborative Group on Arterial Hypertension” - Palomo-Piñón, Silvia; Antonio-Villa, Neftali Eduardo; Rangel-Zertuche, Ricardo Alfonso; Berumen-Lechuga, María Guadalupe; Medina-Serrano, Julio Manuel; García-Cortés, Luis Rey; Mejia-Rodríguez, Oliva; León-Vázquez, María de la Luz; González-Dzib, Roxana del Socorro; González-Coronado, Vidal José; Álvarez-Aguilar, Cleto; Paniagua-Sierra, José Ramón; et al. (Frontiers in Public Health, 2024)
Background Arterial hypertension is highly prevalent in Mexico; nevertheless, there are limited insights regarding its management during the COVID-19 pandemic. Here, we estimate the prevalence of clinical and treatment profiles of arterial hypertension and explore associated factors for undiagnosed and uncontrolled hypertension using a cross-sectional survey endorsed by the Collaborative Group on Arterial Hypertension from the Mexican Institute of Social Security. Methods Our survey was conducted from May to November 2021 using the May-Measurement Month 2021 protocols of the International Society of Hypertension. Arterial hypertension (defined as: blood pressure [BP] ≥140/90 mmHg, previous diagnosis, or taking antihypertensives) and its clinical and treatment profiles were classified according to the World Hypertension League Expert Committee. Mixed-effects logistic regression models were used to explore associated factors for undiagnosed and uncontrolled hypertension. Results Among 77,145 screened participants (women: 62.4%; median age: 46 [IQR: 32–59] years), the prevalence of arterial hypertension was 35.7% (95% CI: 35.3–36.0, n = 27,540). Among participants with arterial hypertension, 30.9% (95% CI: 30.4–31.5, n = 8,533) were undiagnosed, 6.6% (95% CI: 6.3%−6.9%, n = 1,806) were diagnosed but untreated, 43.4% (95% CI: 42.9–44.0, n = 11,965) had uncontrolled hypertension, and only 19% (95% CI: 18.6%−19.5%, n = 5,236) achieved hypertension control (BP < 130/80 mmHg). Explored associated factors for undiagnosed and uncontrolled hypertension include being men, living in the central and southern regions, lower educational attainments, higher use of pharmacological agents, and previous COVID-19 infection. Conclusion Our findings suggest that adverse arterial hypertension profiles, mainly undiagnosed and uncontrolled hypertension, were highly prevalent during the context of the COVID-19 pandemic in Mexico.